Factors that influence the Wadiah and Mudharabah as Islamic banking products: case study CIMB Islamic Bank / Azariah Ibrahim - Ibrahim, Azariah (Faculty of Business and Management, 2012)
This paper investigate the factors that influencing the Wadiah & Mudharabah as Islamic banking products offered by CIMB Islamic Bank. Questionnaire was carried out on respondents to collect the data and its involved 60 respondents which is customer and staff CIMB bank. To complete this research, primary and secondary data will used which is questionnaire and several technique like frequency analysis, reliability analysis, correlation analysis and regression analysis. This research focuses on two factors which are awareness and perception towards Wadiah and Mudharabah Islamic products. Furthermore, research also proved that the awareness and perception an important to influence the Wadiah and Mudharabah Islamic banking products. From the researcher finding, it show that the relationship between independent variables (awareness and perception) and dependent variable (preferences that influence the Islamic banking). Lastly, hope this report can give valuable information about the factors that influence the Wadiah and Mudharabah Islamic banking products towards customers